2017
DOI: 10.1177/2050312117727444
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of lymph node mapping with indocyanine green in robotic gastrectomy for gastric cancer

Abstract: Objectives:Robotic gastrectomy has become increasingly popular in the treatment of gastric cancer, especially in Asian countries. The use of indocyanine green fluorescence has been reported in lymphatic mapping for gastric cancer in laparoscopic gastrectomy; however, there have been few reports regarding the use of indocyanine green in robotic gastrectomy.Methods:From January 2011 to March 2016, a total of 79 patients underwent robotic gastrectomy for gastric cancer. Among them, intraoperative subserosal injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 18 publications
(39 reference statements)
3
36
0
Order By: Relevance
“…Our study found that ICG is not associated with increased incidence of perioperative complications, which is consistent with previous literature [15][16][17]25 . We also found that the postoperative hospital stay was similar between two groups, which prompted similar recovery process.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our study found that ICG is not associated with increased incidence of perioperative complications, which is consistent with previous literature [15][16][17]25 . We also found that the postoperative hospital stay was similar between two groups, which prompted similar recovery process.…”
Section: Discussionsupporting
confidence: 93%
“…Traditionally, ICG administration includes subserosal and submucosal injections around the tumor [14][15][16][17]25 . Previous studies suggested that submucosal injection is superior than subserosal injection in intraoperative lymph node detection 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more false‐positive lymph nodes were found than anticipated due to spread of the contrast agent through lymphatic vessels to second‐tier lymph nodes . Hence, no additional value of the NIRF was observed, since still too many lymph nodes were unnecessarily resected …”
Section: Sln Identification In Gastric Cancermentioning
confidence: 98%